If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -12 = 10 + -1x Reorder the terms: -12 + 3x = 10 + -1x Solving -12 + 3x = 10 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. -12 + 3x + x = 10 + -1x + x Combine like terms: 3x + x = 4x -12 + 4x = 10 + -1x + x Combine like terms: -1x + x = 0 -12 + 4x = 10 + 0 -12 + 4x = 10 Add '12' to each side of the equation. -12 + 12 + 4x = 10 + 12 Combine like terms: -12 + 12 = 0 0 + 4x = 10 + 12 4x = 10 + 12 Combine like terms: 10 + 12 = 22 4x = 22 Divide each side by '4'. x = 5.5 Simplifying x = 5.5
| 7b+7=0 | | -5x(x+1)=13 | | 2a-3.5=3 | | 9*0+2y=-72 | | 12+12L-1.5L^2=0 | | (1/8)^(2/3) | | 9*-8+2y=-72 | | 3n+2.5=3.5 | | 168+c=100 | | 9*4+2y=-72 | | x^2+8x=513 | | 336+4c=268 | | 4-(50-7.5)= | | 6y^2-7y+16-12y^2-7y-6= | | 2*168=p | | z^2-z+iz+i=0 | | 4*1.6-2.6=9 | | 1.3*1.6+3.7*1.6=8 | | g(5a)= | | 4v=8/7 | | 2x+0.75=5 | | (5x+2)(3x^2-4x+1)=0 | | -5x+(x+1)=13 | | 0.14+0.3=0.85 | | p+78=115 | | 5w^7x^8*3xv^6*5w^7v^8= | | 13*6=g | | 3m-2m=15 | | 0.2496/0.12 | | 76(y-72)=y-65 | | 3x+4=0.6 | | 3/7=n/24 |